2014
DOI: 10.1155/2014/694565
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Stigma and Associated Factors among People with Schizophrenia at Amanuel Mental Specialized Hospital, Addis Ababa, Ethiopia: A Cross-Sectional Institution Based Study

Abstract: Background. While effective treatments are available for people with schizophrenia, presence of perceived stigma prevents them from accessing and receiving the help they need to get. Objectives. To assess the prevalence and associated factors of perceived stigma among people with schizophrenia attending the Outpatient Department of Amanuel Mental Specialized Hospital, Addis Ababa, Ethiopia. Methods. Institution based cross-sectional study design was conducted among 411 subjects using an Amharic version of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 22 publications
2
28
3
Order By: Relevance
“…This result is consistent with the reported magnitude of high perceived stigma in studies carried out among schizophrenia and schizoaffective disorder patients in Austria 66.9% [44], a meta-analysis report of the magnitude perceived stigma among schizophrenia patients in the USA, which revealed a rate of 64.55% [22], and the magnitude of self-stigma among schizophrenia spectrum disorders in Czech-Republic was 63.32% [45]. However, this finding was lower than that in the study conducted in Ethiopia, where prevalence of higher perceived stigma was reported at 83.5% before 6 years back by using the perceived devaluation and discrimination scale and in this study, factors associated with perceived stigma completely different from the previous study [9]. Another study conducted in southern California showed that 80% of people with schizophrenia had experienced perceived stigma [46].…”
Section: Discussioncontrasting
confidence: 96%
See 4 more Smart Citations
“…This result is consistent with the reported magnitude of high perceived stigma in studies carried out among schizophrenia and schizoaffective disorder patients in Austria 66.9% [44], a meta-analysis report of the magnitude perceived stigma among schizophrenia patients in the USA, which revealed a rate of 64.55% [22], and the magnitude of self-stigma among schizophrenia spectrum disorders in Czech-Republic was 63.32% [45]. However, this finding was lower than that in the study conducted in Ethiopia, where prevalence of higher perceived stigma was reported at 83.5% before 6 years back by using the perceived devaluation and discrimination scale and in this study, factors associated with perceived stigma completely different from the previous study [9]. Another study conducted in southern California showed that 80% of people with schizophrenia had experienced perceived stigma [46].…”
Section: Discussioncontrasting
confidence: 96%
“…In another study conducted in 14 European countries, the prevalence of stigma was 41.7% among schizophrenia patients [8]. In Ethiopia, the prevalence of stigma among people with mental illness were reported to be within the range of 32.1% to 83.5% [9,10].…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations